He just goes on forever – The vampire between the poles of Cultural Transfer (KULT_online, 2013)
Daniela Soloviova-Horville, a French expert in comparative literature studies, approaches the cross-bordering figure of the vampire by also crossing disciplinary borders: in Les vampires. Du folklore slave à la littérature occidentale based on her doctoral thesis, she assembles textual material belonging to several European language and cultural areas and innovatively combines different methods borrowed from ethnology, the history of ideas, and literary studies. She strictly focuses an historical perspective for a double aim: on the one hand she places the various ideas of the vampire appearing in folklorist and literary traditions as well as in erudite milieus into History; on the other she connects them with contemporary socio-cultural phenomena. In this way, Soloviova-Horville manages not only to make comprehensible the vampire's representations in his dominant figuration as a bloodsucker but also to free him of this idea: She shows that it is exactly his ability to metamorphose that secures the 'species'' survival.